«Det dukket op[p] en fremmed i byen…»: Knut Hamsuns «Mysterier» og Guram Gegeshidzes «En synder» - Loria, Kakhaber (Nordlit, 2016)
Knut Hamsun has always been regarded as an important prose writer in Georgia, admired for his unique literary gifts. His novel Mysteries and its enigmatic protagonist, Nagel, have especially fascinated Georgian readers. Guram Gegeshidze (1934–) is one of the best-known novelists in post-Stalinist Georgia. His novel, A Sinner was written in 1966. That there is «something Scandinavian» in A Sinner and that the novel even bears a resemblance to Hamsun’s Mysteries was pointed out almost as soon as the novel was published. In spite of this, A Sinner is quite clearly an independent work with an intrinsic value of its own and its own characteristic inner logic. When A Sinner was written, there was a renewed interest in the modernist tendencies that had arisen in the years before the Soviet occupation of 1921. When we bear in mind that Hamsun’s writings of the 1890s have always been particularly popular in Georgia, it is not so surprising that one of the best Georgian novels from a period that may be characterized as a new wave of Georgian modernism has such a creative and interesting relationship with Hamsun’s masterpiece.